Bondfree Will sebagai Tinjauan Teologis atas Relasi antara Kehendak Terikat dan Kehendak Bebas Manusia - Simamora, Tommy Hasoloan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
The concepts of free will and bound will are important theological issues that have been debated since the time of the Church Fathers through the Reformation era and remain relevant in postmodern discourse. This study aims to analyze the views of Augustine and Martin Luther on the relationship between human freedom and bondage, particularly in the context of sin, grace, and salvation. Using a qualitative method with a literature review approach, this study examines relevant primary and secondary works to compare the two perspectives. The findings reveal that Augustine acknowledges the corrupted human will yet retains the capacity to respond to grace, while Luther emphasizes the total bondage of human will to original sin, rendering humanity incapable of choosing good without divine grace. As a synthesis, the concept of BondFree Will is introduced to bridge the tension between the freedom to choose and bondage to sinful nature, emphasizing that true freedom can only be found in bondage to God's grace.